PARAMETRIC OPTIMIZATION OF OIL PALM MESOCARP FIBER VALORIZATION WITH HYBRID OZONATION-ULTRASONIC PRETREATMENT METHOD - Didi Dwi Anggoro; Kusuma Dewi, Indahsari; Luqman Buchori; Aji Prasetyaningrum (IIUM Engineering Journal, 2023)
Oil palm mesocarp fiber is a promising lignocellulosic biomass as a raw material for valorizing biomass into more valuable products such as second-generation biofuels, biocomposites, or bioenergy. However, the lignin composition present in lignocellulosic biomass provides resistance to the valorization process and protects the cellulose composition, thereby limiting the conversion of cellulose into more valuable products. The hybrid ozonation-ultrasonic method as a lignin-degrading method is starting to be considered an effective method. Additionally, a Box-Behnken Design (BBD) was employed to investigate each independent variable's effect on pretreatment process conditions using the response surface methodology (RSM), namely reaction time (30-90) min, reaction temperature (20 -40) oC and ozone flow rate (1-3) L/min to the response of the percentage of lignin degradation (%). The optimum condition of the pretreatment process is determined using the desirability function graph. The results showed that reaction time, reaction temperature, and ozone flow rate had a significant effect on lignin degradation (p <0.05). The optimum conditions obtained the highest percentage of lignin degradation, namely 92.08% at a reaction temperature of 30 oC with an ozone flow rate of 2 L/min for 60 minutes reaction time. The decrease in lignin absorption peaks at 1638 cm-1 and 1427 cm-1 was supported by the results of the analysis of increased crystallinity in the sample after the pretreatment of lignin degradation to 80.20% and was validated by changes in the morphology of the mesocarp fiber after the pretreatment process indicating that the lignin compound had been successfully degraded from cellulose products of mesocarp fibers. ABSTRAK: Sabut gentian kelapa sawit berpotensi sebagai bahan mentah biojisim lignoselulosa bagi menambah nilai produk biojisim seperti bahan bio api generasi kedua, biokomposit atau biotenaga. Walau bagaimanapun, komposisi lignin yang wujud dalam biojisim lignoselulosa menentang proses tambah nilai dan melindungi komposisi selulosa, dengan itu mengehadkan penukaran selulosa kepada produk yang lebih berharga. Kaedah hibrid ozonasi-ultrasonik sebagai kaedah merendahkan lignin, mula mendapat perhatian sebagai kaedah berkesan. Selain itu, Reka Bentuk Kotak-Behnken (BBD) telah digunakan bagi menyiasat setiap kesan pembolehubah bebas pada keadaan proses prarawatan menggunakan kaedah permukaan tindak balas (RSM), iaitu masa tindak balas (30-90) min, suhu tindak balas (20 -40) oC dan kadar aliran ozon (1-3) L/min terhadap tindak balas pada peratusan degradasi lignin (%). Keadaan optimum bagi proses prarawatan ditentukan menggunakan graf fungsi keboleh inginan. Dapatan kajian menunjukkan bahawa masa tindak balas, suhu tindak balas, dan kadar aliran ozon mempunyai kesan yang signifikan terhadap degradasi lignin (p<0.05). Keadaan optimum peratusan degradasi lignin tertinggi adalah pada 92.08% pada suhu tindak balas 30 oC dengan kadar aliran ozon 2 L/min selama 60 minit masa tindak balas. Penurunan puncak penyerapan lignin pada 1638 cm-1 dan 1427 cm-1 disokong oleh keputusan analisis peningkatan kehabluran sampel selepas prarawatan degradasi lignin sebanyak 80.20% dan telah disahkan oleh perubahan morfologi sabut gentian selepas proses prarawatan menunjukkan bahawa sebatian lignin telah berjaya didegradasi daripada produk selulosa sabut gentian.